Chlorhexidine rinse for prevention of urethritis in men linked to oral sex - Kolahi, Jafar; Abrishami, Mohamadreza; Fazilati, Mohamad; Soolari, Ahmad (International archives of medicine, 2010)
Oral sex among teenagers is on the rise. Similarity between the oral flora and organisms recovered from nongonococcal urethritis and prostatitis, points to retrograde entry of bacteria from oral cavity into the urethra following insertive oral intercourse. Chlorhexidine has a wide spectrum of anti-bactericidal activity encompassing gram positive and negative bacteria. It is also effective against HIV and HBV. It produced large and prolonged reductions in salivary bacterial counts within 7-h of its use. Hence, it would seem logic to postulate that rinsing with chlorhexidine before oral sex will be effective for prevention of retrograde entry of bacteria from oral cavity into the urethra. The recommendation for rinsing will be: 15 ml of a 0.12% or 10 ml of 0.2% chlorhexidine rinse for 30 seconds. Also other drug delivery systems such as chlorhexidine chewing gum or spray can be used. Men suffering from recurrent nongonococcal urethritis or prostatitis are good subjects for testing the hypothesis. They perform genital safe sex via consistent use of condom. Yet they generally received unprotected insertive oral intercourse. Chlorhexidine can be used for prevention of recurrences of the disease. The chlorhexidine will be a new, easy, attractive and effective method for reduction of nongonococcal urethritis, prostatitis and epidydimitis following insertive oral intercourse. It is poorly absorbed from skin, mucosa and gastrointestinal tract indicating systemic safety of chlorhexidine. The agent does not cause any bacterial resistance and supra-infection.